Posterior cingulate cortex hyperactivity in conversion disorder: a PET/MRI study - Tatlı, Safiye Zeynep; Araz, Mine; Özkan, Elgin; Peker, Elif; Erden, Mehmetİlhan; Cankorur, VesileŞentürk (Frontiers in Psychiatry, 2024)
Introduction Several neuroimaging studies have been conducted to demonstrate the specific structural and functional brain correlations of conversion disorder. Although the findings of neuroimaging studies are not consistent, when evaluated as a whole, they suggest the presence of significant brain abnormalities. The aim of this study is to investigate brain metabolic activity through F-18 fluorodeoxyglucose PET/MRI in order to shed light on the neural correlates of conversion disorder. Methods 20 patients diagnosed with conversion disorder were included in the study. Hamilton Depression and Anxiety Rating Scales, Somatosensory Amplification Scale and Somatoform Dissociation Scale were administered. Then, brain F-18 FDG-PET/MRI was performed.. Results Hypermetabolism was found in posterior cingulate R, while glucose metabolisms of other brain regions were observed to be within the normal limits. When compared with the control group, statistically significant differences in z-scores were observed among all brain regions except for parietal superior R and cerebellum. No correlation was observed between the metabolisms of the left ACC and left medial PFC; left ACC and left temporal lateral cortex; cerebellum and left parietal inferior cortex despite the presence of positive correlations between these regions in the opposite hemisphere. Discussion Results of the study suggest a potential involvement of the DMN which is associated with arousal and self-referential processing as well as regions associated with motor intention and self-agency.